Probing the Progenitor of High-z Short-duration GRB 201221D and its Possible Bulk Acceleration in Prompt Emission. (1st July 2022) - Yuan, Hao-Yu; Lü, Hou-Jun; Li, Ye; Zhang, Bin-Bin; Sun, Hui; Rice, Jared; Yang, Jun; Liang, En-Wei
Abstract: The growing observed evidence shows that the long- and short-duration gamma-ray bursts (GRBs) originate from massive star core-collapse and the merger of compact stars, respectively. GRB 201221D is a short-duration GRB lasting ∼0.1 s without extended emission at high redshift z = 1.046. By analyzing data observed with the Swift/BAT and Fermi/GBM, we find that a cutoff power-law model can adequately fit the spectrum with a soft E p = 113 − 7 + 9 keV, and isotropic energy E γ, iso = 1.36 − 0.14 + 0.17 × 10 51 erg . In order to reveal the possible physical origin of GRB 201221D, we adopted multi-wavelength criteria (e.g., Amati relation, ε -parameter, amplitude parameter, local event rate density, luminosity function, and properties of the host galaxy), and find that most of the observations of GRB 201221D favor a compact star merger origin. Moreover, we find that α ˆ is larger than 2 + β ˆ in the prompt emission phase which suggests that the emission region is possibly undergoing acceleration during the prompt emission phase with a Poynting-flux-dominated jet.